Projeto - Conhecendo as plantas ornamentais - Boaventura, Renivaldo; Ribeiro, Geni; Bordinhão, Andréa Chiozini; Nogueira, Nelci; Oliveira, Maria Auxiliadora de; Santos, Marlene Alves dos; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PFD